vLeadership in Marriage and Family Therapy Programs is Under-Explored: A Thematic, Narrative Overview - Stephanie M Morgan (Westcliff International Journal of Applied Research, 2020)
Institutions of higher education rely on identified leaders to continue the mission of the organization, hire and retain quality faculty and staff, and sustain and further develop vigorous academic programs that retain students and prepare graduates to enter the work force. Discipline specific departments are subject to many demands and resources are pulled in different directions. As a result, the body of literature on leadership in higher education is robust and diverse. However, research on leadership in graduate marriage and family therapy programs is paltry in addressing if a relationship exists between leaders and student capacity to employ skills in a field focused on relationships. This study was a thematic, narrative overview. An exhaustive search of literature was conducted over the span of four years. Articles were assessed for relevance and appropriateness, organized by theme, and the findings were consolidated and are presented within this article. The three identified themes were: leadership in higher education, rigor in marriage and family therapy programs, and leadership in marriage and family therapy programs and other mental health fields. Gaps were identified in the literature and include the role of leadership style identification and self-exploration, the extent to which program leaders interact with students, and how the relationship between administrators and students impacts the development of field related skills.